Metachronous bilateral testicular cancer: Case reports and review of literature. Issue 4 (November 2019) - Low, Zhi-Yang; Yan, Angela; Arul, Dhili; Chitale, Sudhanshu
Background: It is well recognised that men with unilateral testicular cancer may go on to develop metachronous cancer in the contralateral testis. Here, we present two cases of metachronous bilateral testicular cancer and a literature review. Clinical cases: In both cases, the second testicular cancer occurred several years after the initial cancer, and both cases were not screened for presence of contralateral germ cell neoplasia in situ upon the first diagnosis. Discussion: We also present a literature review on the need for screening biopsies of contralateral testis for germ cell neoplasia in situ and the risk factors which should encourage screening. Furthermore, we also explore the effect of chemotherapy on the incidence of contralateral testicular cancer and the effectiveness of radiotherapy in the treatment of germ cell neoplasia in situ. Conclusion: We believe that screening biopsies of the contralateral testis upon diagnosis of unilateral testicular cancer should be encouraged as it can lead to better management of the condition and a relatively favourable outcome on functional fronts.